Designed Study Desk with Skincare Storage and Wireless Speaker - Fatmawati, Anggi (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
The demand for multifunctional furniture continues to grow, particularly among university students living in dormitories or small rooms. This study developed a folding study desk that functions not only as a workspace but also integrates storage space for skincare products and a wireless speaker. The aim is to create a space-efficient and aesthetically appealing solution tailored to the needs of the younger generation. The research employed a Research and Development (R&D) approach, involving stages of problem identification, data collection, product design, design validation, revision, and product testing. The findings indicate that this innovative desk provides a practical solution by combining study, grooming, and entertainment functions in a single unit. User feedback confirms its relevance for students who require compact and functional furniture. The product demonstrates significant commercial potential due to its strong market value in the modern furniture sector and its unique combination of features rarely found in a single piece. Furthermore, its design emphasizes portability, ease of use, and style, aligning with contemporary lifestyle trends. The product effectively meets both the functional and emotional needs of users, making it not merely a tool but also a lifestyle item that supports productivity and personal care.